If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (z + -1)(2Z + 3) = 0 Reorder the terms: (-1 + z)(2Z + 3) = 0 Reorder the terms: (-1 + z)(3 + 2Z) = 0 Multiply (-1 + z) * (3 + 2Z) (-1(3 + 2Z) + z(3 + 2Z)) = 0 ((3 * -1 + 2Z * -1) + z(3 + 2Z)) = 0 ((-3 + -2Z) + z(3 + 2Z)) = 0 (-3 + -2Z + (3 * z + 2Z * z)) = 0 (-3 + -2Z + (3z + 2zZ)) = 0 (-3 + -2Z + 3z + 2zZ) = 0 Solving -3 + -2Z + 3z + 2zZ = 0 Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '3' to each side of the equation. -3 + -2Z + 3z + 3 + 2zZ = 0 + 3 Reorder the terms: -3 + 3 + -2Z + 3z + 2zZ = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2Z + 3z + 2zZ = 0 + 3 -2Z + 3z + 2zZ = 0 + 3 Combine like terms: 0 + 3 = 3 -2Z + 3z + 2zZ = 3 Add '-3z' to each side of the equation. -2Z + 3z + -3z + 2zZ = 3 + -3z Combine like terms: 3z + -3z = 0 -2Z + 0 + 2zZ = 3 + -3z -2Z + 2zZ = 3 + -3z Reorder the terms: -3 + -2Z + 3z + 2zZ = 3 + -3z + -3 + 3z Reorder the terms: -3 + -2Z + 3z + 2zZ = 3 + -3 + -3z + 3z Combine like terms: 3 + -3 = 0 -3 + -2Z + 3z + 2zZ = 0 + -3z + 3z -3 + -2Z + 3z + 2zZ = -3z + 3z Combine like terms: -3z + 3z = 0 -3 + -2Z + 3z + 2zZ = 0 The solution to this equation could not be determined.
| -6(-2n-6)=84 | | 5(e-7)=20 | | n^2=x | | (2x)+12=(4x)-12 | | y+3+7-9=90 | | u(x)=-2*300+1000 | | 7y-9=y+3 | | u(x)=-2x+1000 | | 30x-20/5 | | -92=-5v-7(v+8) | | Log(g)= | | (6+4x)=(4x-6) | | x-24=5x+6 | | xLog(n)= | | 5x^2-6x-100=0 | | (A^3/-2b)^2 | | (D^4-5d^2+4)y=0 | | 16x+3y-13x+14y= | | 4^7/4^2 | | z^4-iz^3+8z-8i=0 | | x-2/(2x^2)^2=0 | | 9x[x+1]=4 | | x^4-3x^3+7x^2+5x-9=0 | | (x-6)(x-3)=-2 | | a^2-8a=-16 | | 2(3x+6x)=25 | | 102/4 | | 105=-5(4b+7) | | (X+30)+(180-3x)+(1X)=180 | | 5v=11+3u | | 3-(-6x)=4x+9 | | 2cosx-4=0 |